Stages of the embryonic development of the piavuçu Leporinus macrocephalus (Garavello & Britski, 1988) - Reynalte-Tataje, David (2008)
Understanding the embryogenesis of a species is a useful tool for locating areas for spawning and for the study of growth of the species in their natural environment. This study was conducted at the Panamá Fish Hatchery in Santa Catarina, Brazil, to characterize the embryonic development of the piavuçu Leporinus macrocephalus (Characiformes, Anostomidae). Description was based on the analysis of embryos collected at 10-minute intervals during the first three hours after fertilization, and later at 30-minute intervals until larva hatching. Piavuçu eggs are detached, transparent, small, spherical, with a large perivitelline space. Hatching takes place 11 hours and 30 minutes after fertilization at an average temperature of 28.2ºC. Total length and weight of recently hatched larva were 2.39 ± 0.12 mm, and 0.5 ± 0.1mg respectively.